ANALISIS PERUBAHAN PENGGUNAAN LAHAN DI WILAYAH PERENCANAAN II (WP II) KOTA BANDARLAMPUNG TAHUN 2011-2021 DAN PREDIKSI PENGGUNAAN LAHAN PADA TAHUN 2026 MENGGUNAKAN METODE CELULLAR AUTOMATA - Ryansyah Izhar; Hasibuan, Yosafat Christ; Oetomo, Andi (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
Land use is the result of human intervention in natural resources, particularly land, to meet both material and spiritual needs (Asyad, 1989 in As-SYAKUR, 2008). Changes in land use patterns in a region are influenced by several factors, including population growth, accessibility levels, infrastructure development, and local economic conditions. Planning Zone II (WP II) of Bandar Lampung City, designated as a center for higher education, a key land transportation hub, as well as an additional location for industry, urban settlements, urban infrastructure, trade, and services in the Spatial Planning (RTRW) of Bandar Lampung City for the years 2021-2041, has experienced a significant increase in population and density. Therefore, changes in land use in this area are expected to continue. Recent research is needed to understand the dynamics of these changes, the factors influencing them, and to forecast land use patterns over the next five years. This research adopts a deductive approach using quantitative methods, with data collection from various relevant secondary sources. Data analysis includes spatial analysis, descriptive analysis, and multiple linear regression analysis. The findings of the study show that the changes in land use patterns in Planning Zone II of Bandar Lampung City from 2011 to 2021 have been significant, with population growth and accessibility levels playing crucial roles in Bandar Lampung City. Therefore, land use modeling has been conducted to predict changes that may occur over the next five years, as a basis for recommending a review of the Spatial Planning (RTRW) of Bandar Lampung City for the years 2021-2041.